Current Stage and Prospects of Industrial and Innovative Development in Kazakhstan - TYO, Alexsandr; KOGAY, Galina; JAZYKBAYEVA, Baldyrgan; SPANOVA, Bahit; TEN, Tatyana; OMAROVA, Sholpan (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article examines the analysis of modern state of industry in Kazakhstan. Also had decrypted the methods of formation of national system of venture financing to accelerate the industrial and innovative development of Kazakhstan. Problems statement in recent years owing to the taken measures of the state innovation has been identified as strategically important directions of development of the Republic of Kazakhstan. It is necessary to conduct a full audit and optimization, both managerial and operational business processes. In the end, it must become highly efficient, compact and professional. Management quality and corporate governance needs to be tightened up to the international level. We should attract funding from non-governmental sources on the implementation of the programs. The great potential for development of entrepreneurship network expansion public-private partnership. We are talking about the transfer of a number of public services to business. To attract private capital need to use all possible types and forms of public-private partnership: trust management of state property, service contracts and other.